2019
DOI: 10.1186/s13567-019-0626-2
|View full text |Cite
|
Sign up to set email alerts
|

Transmission studies of chronic wasting disease to transgenic mice overexpressing human prion protein using the RT-QuIC assay

Abstract: Chronic wasting disease (CWD) is a fatal prion disease which infects deer, elk and moose. CWD was first described as a wasting syndrome in captive deer in Colorado and Wyoming wildlife facilities from 1967 to 1979. Currently, CWD has been reported in 26 states of the USA, three Canadian provinces, South Korea, Norway and Finland. Since human consumption of cervids is common, it is critical to determine if CWD can infect humans. Published research, including epidemiologic studies and transmission studies using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 40 publications
2
45
1
Order By: Relevance
“…For both mouse strains, the majority of cases inoculated caused clinical disease in at least some of the mice. As expected, disease incubation times were generally shorter in the tg66 mice which express higher levels of human PrP C -M129 when compared to the tgRM mice [38]. Only two samples, case 4 and the CC sample from case 9, failed to cause any clinical disease within the lifetime of the host, although neuropathology and PrP Sc deposition were observed in a few mice suggesting that clinical disease may have eventually developed in those animals.…”
Section: Transmission Of MV Heterozygous Cases Of Scjd and Icjd Into supporting
confidence: 63%
“…For both mouse strains, the majority of cases inoculated caused clinical disease in at least some of the mice. As expected, disease incubation times were generally shorter in the tg66 mice which express higher levels of human PrP C -M129 when compared to the tgRM mice [38]. Only two samples, case 4 and the CC sample from case 9, failed to cause any clinical disease within the lifetime of the host, although neuropathology and PrP Sc deposition were observed in a few mice suggesting that clinical disease may have eventually developed in those animals.…”
Section: Transmission Of MV Heterozygous Cases Of Scjd and Icjd Into supporting
confidence: 63%
“…Nevertheless, Race et al. () recently published a study performed with two lineages of humanised mice that provided intriguing results. They exposed tgRM and tg66 mice, which overexpress MM human PrP at levels two‐ to fourfold and 8‐ to 16‐fold higher than the physiological levels, respectively, to different CWD sources.…”
Section: Assessmentmentioning
confidence: 99%
“…These two models harbour the highest levels of PrP c expression among all those that have been tested in these studies. Among these mice, 7% (3/45) tgRM and 30% (15/52) tg66 mice fitted the ‘criteria as prion disease suspects’ that the authors considered to be relevant and that correspond to ‘signs of wasting, weakness, neurologic disease and behavioural changes’ (Race et al., ). Extensive analyses of the brains of these animals did not provide any lesional, biochemical or immunohistochemical element that could confirm the diagnosis of prion disease and the authors expressed some reservations about the relevance of those observations because of the advanced age of these animals (> 500 days of incubation).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…OM sampling provides direct access to olfactory neurons and thus to one of the sites, that is currently regarded as one of the potential initiation points of seeding and spread of pathological α-syn assemblies in Parkinson's disease. RT-QuIC for α-syn detects disease-associated α-syn aggregates in billion-fold diluted brain tissue preparations from different α-synucleinopathies (Groveman et al, 2018) with a higher sensitivity than conventional immunohistochemistry, as shown in prion diseases (Race et al, 2019). RT-QuIC results are classified as negative or positive based on the extent of α-syn aggregates seeding and do not depend on observer evaluation, as occurs for -syn immunohistochemistry in skin biopsies of patients with iRBD (Donadio et al, 2019).…”
Section: Discussionmentioning
confidence: 99%